Befolkningens holdninger til markedsgørelse af den offentlige sektor: erkendelsesinteresser og forklaringsmodeller i politologien - Lindholst, Andrej Christian; Hansen, Morten Balle (Politik, 2015)
Privatization policies in the public sector can still, after 30 years on the public management reform agenda, cause outcries among Danes. ere is, however, a genuine lack of theoretically informed research that explores public opinion on privatizations. In this article we review the scarce international literature with the purpose of providing an informed theoretical foundation for future research on the public opinion on privatizations. We nd that the research eld is characterized by a limited number of studies, four research interests as mo- tivation as well as four explanatory factors as foundation for exploring the formation of public opinions. e research eld is furthermore biased toward certain forms of privatizations as well as certain policy sectors. We recommend that the research eld should be further developed by a future focus on under-explored forms of privatization and a greater attention to comparisons across di erent policy areas.